Valley of the Moon : the diary of Maria Rosalia de Milagros - Garland, Sherry (Dear America, 2001)
The 1845-1846 diary of thirteen-year-old Maria, servant to the wealthy Spanish family which took her in when her Indian mother died. Includes a historical note about the settlement and early history of California.